Ectopic dendrites occur only on cortical pyramidal cells containing elevated GM2 ganglioside in alpha-mannosidosis. - Goodman, L A (1991)
In a variety of neuronal storage diseases, cortical pyramidal cells elaborate ectopic dendrites at the axon hillock. A feature common to all the diseases characterized by ectopic dendrites is an elevated level of GM2 ganglioside in cerebral cortex. In cats with one such disease, alpha-mannosidosis, the number of pyramidal cells bearing ectopic dendrites is small; the present study shows that GM2 ganglioside is stored only in those pyramidal neurons exhibiting ectopic dendrites. Using a Golgi-electron microscopy method with periodic acid-Schiff (PAS) staining, we first established that pyramidal cells bearing ectopic dendrites contained PAS+ membranous inclusions, consistent with storage of glycolipids. In contrast, those with smooth axon hillocks accumulated PAS- floccular inclusions, consistent with storage of oligosaccharides. Next, application of a monoclonal antibody against GM2 ganglioside revealed that subsets of both pyramidal and intrinsic neurons contained GM2-like immunoreactivity. Every GM2+ cell contained PAS+ membranous inclusions, indicating that pyramidal cells bearing ectopic dendrites stored GM2 ganglioside. In cats with alpha-mannosidosis induced by swainsonine, some pyramidal neurons showed GM2-like immunoreactivity after 4 weeks of treatment, whereas ectopic dendrites only became evident after 7 weeks of treatment. Thus, GM2 ganglioside accumulated in pyramidal neurons before ectopic dendrites emerged from the axon hillock. We propose that the reinitiation of dendrite growth on mature pyramidal cells is brought about by accumulated GM2 ganglioside.